An analysis of the contribution of four painters to the development of contemporary Zambian painting from 1950-1997 - Setti, Godfrey (Rhodes University, Faculty of Humanities, Department of Fine Art, 2001)
This study presents an analysis of the contribution of four painters to the development of contemporary Zambian painting, from 1950 to 1997. This is preceded by a brief history of Zambian painting, including Bushmen rock painting and early Bantu art, which is followed by an account of the way western influence, introduced by the white man, started changing the style of painting in the country as it began to affect indigenous artists. In the work of artists who began painting from about 1900 to 1950, both western and traditional stylistic influences can be seen. While the painters whose work is analysed in this thesis had some knowledge of Zambian art before 1950, they were mainly influenced by western ideas of painting. From a list of more than ten painters ofthis period from 1950 to 1997, I selected: Gabriel Ellison, Cynthia Zukas, Hemy Tayali and Stephen Kappata because I know them personally and therefore had access to them and their work, which facilitated my analysis of their work and its contribution to Zambian painting. This analysis takes the form of four chapters, one for each artist, in which relevant biographical and educational background is outlined, followed by an analysis of examples ofvork. Finally, ways in which each painter, through exposure to the Zambian public and artistic community, contributed to further development in Zambian painting, are emphasised.
Keywords: Painting -- Zambia; Art, Zambian -- 20th Century; Painting -- 20th century -- Zambia